Pokémon. Sword & shield. Volume 8 - Kusaka, Hidenori; Tanzer, Molly (Viz Media, LLC, 2023)
After a confrontation with two mystery Trainers, hackers Casey Shield and Henry Sword repair gear for Pokémon and get some help from the Gym Leader of Spikemuth as they head to the Rose Tower to discover the truth about their adversaries.